Legal Status of Test Tube Baby Children: A Legal Review of Lineage and Inheritance Rights - Gia Anesta Putri; Masda Agatha Sari (Veteran Law Review, 2026)
This study aims to analyze the legal status of illegal IVF children born from gamete donation or surrogacy procedures within the dualism of Indonesian Civil Law. The crucial issue discussed is the conflict arising between the principle of conservation of lineage in the Marriage Law and the limitations of inheritance rights in the Civil Code (KUHPerdata), especially considering the express prohibition of illegal procedures by Health Law No. 17 of 2023. The study uses a Normative Juridical method with a statutory, case, and conceptual approach. The main results indicate that children from illegal IVF procedures are categorized as children born out of wedlock, so their inheritance rights are limited to one-third of the portion of legitimate children if recognized. We found a legal conflict: the reactive protection solution through Court Decision No. 46/PPU-VIII/2010 has the potential to create civil and inheritance relations with anonymous gamete donors (biological fathers), this directly contradicts the preventive prohibition in the Health Law. In addition, the surrogacy agreement was confirmed null and void under Article 1320 of the Civil Code. This study concludes the need for regulatory harmonization to clarify the limits of the application of the Constitutional Court Decision in order to ensure legal certainty and the best protection for children's civil rights.